(untitled) (UUM Journal of Legal Studies, 2020)
The decisions of disciplinary authorities in disciplinary proceedings continue to be judicially reviewed on the grounds of their failure to grant an oral hearing to affected public servants albeit there is a well-established principle by the Privy Council in Najar Singh’s case since 1976. Such failure may implicate the deliverance of justice, and affect the reputation and goodwill of the Malaysian government as the major employer in the nation. The constitutional protection of a reasonable opportunity of being heard to public servants under Article 135(2) in the case of dismissal and reduction of rank should be interpreted in the light of the fundamental right to life as enshrined in the Federal Constitution. The purpose of this article is to examine the approaches of the court in determining the right to an oral hearing in disciplinary proceedings against public servants; and whether the administrative decisions of the disciplinary authorities should be subject to judicial review or not. This paper forwarded a submission that the court should adopt a liberal approach in determining the right to an oral hearing in disciplinary proceedings against public servants.